'We did everything we could'– a qualitative study exploring the acceptability of maternal‐fetal surgery for spina bifida to parents. (18th July 2021) - Crombag, Neeltje; Sacco, Adalina; Stocks, Bernadette; De Vloo, Philippe; van der Merwe, Johannes; Gallagher, Katie; David, Anna; Marlow, Neil; Deprest, Jan
Abstract: Objective: To explore the concepts and strategies parents employ when considering maternal‐fetal surgery (MFS) as an option for the management of spina bifida (SB) in their fetus, and how this determines the acceptability of the intervention. Methods: A two‐centre interview study enrolling parents whose fetuses with SB were eligible for MFS. To assess differences in acceptability, parents opting for MFS ( n = 24) were interviewed at three different moments in time: prior to the intervention, directly after the intervention and 3‐6 months after birth. Parents opting for termination of pregnancy ( n = 5) were interviewed only once. Themes were identified and organised in line with the framework of acceptability. Results: To parents opting for MFS, the intervention was perceived as an opportunity that needed to be taken. Feelings of parental responsibility drove them to do anything in their power to improve their future child's situation. Expectations seemed to be realistic yet were driven by hope for the best outcome. None expressed decisional regret at any stage, despite substantial impact and, at times, disappointing outcomes. For the small group of participants, who decided to opt for termination of pregnancy (TOP), MFS was not perceived as an intervention that substantially could improve the quality of their future child's life. Conclusion: Prospective parents opting for MFS were driven by their feelings of parental responsibility. They recognise the fetus as their future child and value information and care focusing on optimising the child's future health. In the small group of parents opting for TOP, MFS was felt to offer insufficient certainty of substantial improvement in quality of life and the perceived severe impact of SB drove their decision to end the pregnancy. Key points: What's already known about this topic? Maternal‐fetal surgery for open spina bifida has the potential to improve long‐term outcomes but at significant procedure‐related fetal and maternal risk; Prospective parents receiving an antenatal diagnosis of open spina bifida, face a range of uncertainties regarding the future of their unborn child, and the options provided pose major ethical challenges. What does this study add? Despite significant impact, maternal‐fetal surgery is highly acceptable for those parents who opt for it; Strong feelings of parental responsibility, direct them to do anything in their power to improve their future child's situation; In the small group of parents who opted for termination of pregnancy, maternal‐fetal surgery was felt to offer insufficient certainty of substantial improvement in quality of life and the perceived severe impact of SB drove their decision to end the pregnancy.